The Ocean, Blue Spaces and Outdoor Learning - Brown, Mike (London : Routledge, 2024)
This book explores the educational dimension of people's engagement with the ocean. Across formal, informal, and nonformal learning contexts, it examines how experiences of the ocean and 'blue spaces' help us to understand ourselves, others, and our place within the natural environment, and the place of the ocean in our sociocultural and political life. Drawing on creative projects from around the world, the book introduces topics as diverse as ocean sailing, migrants' experiences of learning to surf, experiencing seascapes through sounds, and the importance of fostering connections with the sea. It provides examples of innovative teaching and learning practices, and the pedagogical possibilities that engagement with the ocean offers to outdoor studies scholars and practitioners in terms of education, and the enhancement of our well-being and the environment. This is fascinating reading for advanced students, researchers, teachers, and educational practitioners with an interest in outdoor studies, experiential and outdoor learning, leisure and recreation studies, environmental studies, or geography.
Keywords: Ocean; EDUCATION / General; NATURE / General